TRADISI PERKAWINAN SUKU PETALANGAN DI DESA BETUNG KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Anggi Retno Mutia; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Marriage tradition or mating ritual of Malay people especially in Petalangan Tribe at Betung Village, Pangkalan Kuras District, Pelalawan Regency. There are some distinctions in the steps of the marriage ritual because of the culture varieties. In this research, the researcher investigates on how marriage tradition of Petalangan tribe in Desa Betung is done and the changes that happen in the stages of the ritual. This research uses social changes theory, with six persons as the respondents consisting of Batin (the village chief), Ninik mamak (the elder relatives) and people in the society who are involved in the marriage ritual either of two-Petalangan-tribe couple or Petalangan with other tribe couple. The research findings show that there are 17 steps in the marriage ritual of Petalangan tribe, starting with 8 pre-marriage steps, followed by 7 marriage steps and 2 post-marriage steps. In its procession, the marriage tradition of Petalangan tribe has undergone some changes. The changes happen because of some factors; (a) supporting factor – advanced system of formal education; and (b) materialism factor – the influence of other society cultures and cultural assimilations. These factors leads to the mixture of some traditions so that, like it or not, it compromises the marriage system of Petalangan tribe in many or less ways.Keywords: changes,tradition, marriage, Petalangan Tribe.